2019
DOI: 10.1002/cam4.1850
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Fusobacterium nucleatum for the diagnosis of colorectal tumor: A systematic review and meta‐analysis

Abstract: The fecal Fusobacterium nucleatum has been reported as a potential noninvasive biomarker for colorectal tumor in several studies, but its exact diagnostic accuracy was ambiguous due to the wide range of sensitivity and specificity. To assess the diagnostic accuracy of fecal F. nucleatum for colorectal tumor, we searched electronic databases including PubMed, Cochrane Library, Embase, and Web of Science, without any date and language restrictions. Two reviewers independently extracted data and appraised study q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…For instance, as mentioned above, F. nucleatum has consistently been found associated with CRC development and progression, being enriched both in feces of patients with adenoma and CRC as compared to control individuals, as well as in tumoral tissue in comparison with surrounding normal tissue (Castellarin et al, 2012; Flanagan et al, 2014; Kostic et al, 2012; Yu et al, 2017). Consistently, a recent meta-analysis concluded that this sole species could be used as a biomarker for a non-invasive screening in CRC and colorectal adenoma (Zhang et al, 2019). Additional efforts have been conducted to identify bacterial markers to predict the risk of developing CRC in a more efficient way (Ai et al, 2017; Rezasoltani et al, 2018; Zeller et al, 2014), with a claim of similar accuracy to the standard FOBT (Zeller et al, 2014).…”
Section: Microbiome-enabled Early Diagnostics Of Crcmentioning
confidence: 70%
See 1 more Smart Citation
“…For instance, as mentioned above, F. nucleatum has consistently been found associated with CRC development and progression, being enriched both in feces of patients with adenoma and CRC as compared to control individuals, as well as in tumoral tissue in comparison with surrounding normal tissue (Castellarin et al, 2012; Flanagan et al, 2014; Kostic et al, 2012; Yu et al, 2017). Consistently, a recent meta-analysis concluded that this sole species could be used as a biomarker for a non-invasive screening in CRC and colorectal adenoma (Zhang et al, 2019). Additional efforts have been conducted to identify bacterial markers to predict the risk of developing CRC in a more efficient way (Ai et al, 2017; Rezasoltani et al, 2018; Zeller et al, 2014), with a claim of similar accuracy to the standard FOBT (Zeller et al, 2014).…”
Section: Microbiome-enabled Early Diagnostics Of Crcmentioning
confidence: 70%
“…Microbiome in CRC patients is often enriched in pro-inflammatory opportunistic pathogens and microbes associated with metabolic disorders and depleted in butyrate-producing bacteria, which have been shown to be pivotal for the preservation of intestinal homeostasis (Gao et al, 2015; Marchesi et al, 2011). Some bacteria such as Streptococcus gallolyticus (in the past Streptococcus bovis ), F. nucleatum , Escherichia coli , B. fragilis and E. faecalis , have high prevalence in CRC patients as compared to the normal population, whereas genera such as Roseburia , Clostridium , Faecalibacterium and Bifidobacterium are generally depleted in CRC patients (Feng et al, 2015; Gagnière et al, 2016; Gao et al, 2015; Shang and Liu, 2018; Wang et al, 2012; Yu et al, 2017; Zhang et al, 2019). Although there is significant interest in identifying specific oncomicrobes, no single species has been found to be universally present among all individuals with CRC and there is significant variation in microbial composition between individuals (Sears and Garrett, 2014).…”
Section: Relationships Between Gut Microbiome and Colorectal Cancermentioning
confidence: 99%
“…Furthermore, F. nucleatum –positive patients had significantly shorter esophageal cancer survival, and this suggests a potential role as a prognostic biomarker for esophageal cancer; this has also been seen for colorectal cancer . F. nucleatum , normally colonizing the human oral cavity, has been recognized as a pathogen in periodontal diseases, ulcerative colitis, and colorectal cancer . F. nucleatum can stimulate secretion of MMP‐9 and MMP‐13 from epithelial cells, which could be involved in the development of several human malignancies because the degradation of collagen IV in the basement membrane and extracellular matrix facilitates tumor progression, including invasion, metastasis, growth, and angiogenesis, in the esophagus .…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is the only bacteria listed as a class I carcinogen and is the primary cause of noncardia gastric cancer and cardia cancer in Asia . Emerging evidence has suggested that other microbes are associated with some types of cancer, including colorectal cancer (eg, Fusobacterium nucleatum and Escherichia coli ) . Furthermore, other microbes colonizing the human gastrointestinal tract may be related to several diseases, such as diabetes, obesity, and multiple sclerosis …”
Section: Introductionmentioning
confidence: 99%
“…Despite our study found that F. nucleatum levels influence cancer progression or recurrence and are associated with the stemness of cervical cancer cells, there are certain limitations. The dysbiosis of intratumor microbiota has been implicated in tumor development and can play a large role in influencing treatment outcomes for patients with cancers [ 26 , 27 ]. But the mechanism by which this bacterium works needs to be elaborated.…”
Section: Discussionmentioning
confidence: 99%